Pengaruh Kualitas Produk, Influencer Dan Iklan Media Tiktok Terhadap Minat Pembelian Produk Skincare Somethinc Di Kota Malang - Aisyah, Erika Nadilah Nur Mustamilatul; Basalamah, Muhammad Ridwan; Amin, Muh Sirojuddin (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study seeks to assess the impact of product quality, influencers, and TikTok media marketing on the purchasing interest in Somethinc skincare products within Malang City. This research employs a quantitative methodology utilizing an explanatory research design. The study sample comprised 125 respondents chosen by purposive sampling. The employed data analysis method is multiple linear regression. The findings of the study indicate that product quality, influencers, and advertisements on TikTok collectively have a positive and substantial impact on purchase intention. Each of the factors—product quality, influencers, and TikTok media advertisements—individually contributes positively and significantly to the purchase intention for Somethinc skincare products. Keywords: Purchase Intent, Product Quality, Influencer, TikTok Media Ads, Somethinc